2018
DOI: 10.1016/j.cub.2018.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Control of Visual Distraction

Abstract: Due to an unfortunate miscommunication, the acknowledgments and authorship of this publication were incorrect. These corrections represent more accurately the funding, scientific, and technical contributions necessary to accomplish the reported research. The authors apologize for the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 0 publications
6
36
2
Order By: Relevance
“…As the N2pc is by definition a difference between contralateral and ipsilateral responses, the balanced displays used in Experiment 2 may have yielded N2pc waveforms that reflected a combination of responses elicited by the target-colored cue and the simultaneously presented distractor-colored cue. Consistent with this, Hickey, Di Lollo, and McDonald (2009) have suggested that the N2pc is a combination of two ERP components: the N T , a negative ERP component associated with target enhancement, and the P D , a positive ERP component associated with distractor suppression (e.g., Cosman, Lowe, Woodman, & Schall, 2018;Gaspelin & Luck, 2018b). Although in Experiment 2 we were able to measure neural responses separately for contralateral and ipsilateral electrode sites, we were not able to determine whether these responses reflected processing of the target-colored cue, the distractor-colored cue, or a combination of both.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…As the N2pc is by definition a difference between contralateral and ipsilateral responses, the balanced displays used in Experiment 2 may have yielded N2pc waveforms that reflected a combination of responses elicited by the target-colored cue and the simultaneously presented distractor-colored cue. Consistent with this, Hickey, Di Lollo, and McDonald (2009) have suggested that the N2pc is a combination of two ERP components: the N T , a negative ERP component associated with target enhancement, and the P D , a positive ERP component associated with distractor suppression (e.g., Cosman, Lowe, Woodman, & Schall, 2018;Gaspelin & Luck, 2018b). Although in Experiment 2 we were able to measure neural responses separately for contralateral and ipsilateral electrode sites, we were not able to determine whether these responses reflected processing of the target-colored cue, the distractor-colored cue, or a combination of both.…”
Section: Discussionmentioning
confidence: 74%
“…To capture the sequence of these laterality effects, we analyzed mean ERP amplitudes during two time windows: An earlier time window focused on the N T component (200 to 300 ms after cue onset, to match the cuerelated time window analyzed in Experiment 2), and a later time window focused on the P D component (350 to 500 ms after cue onset). Past research has shown that the P D component can vary over a broad time range that depends on the evoking stimulus and experimental task (e.g., Burra & Kerzel, 2014;Cosman et al, 2018;Gaspar & McDonald, 2014;Gaspelin & Luck, 2018a;Hickey et al, 2009;Hilimire et al, 2011;Sawaki, Geng, & Luck, 2012;Sawaki & Luck, 2010). To be sure any P D effect was not cancelled out by the opposite polarity of the N T component, we chose a time window that was outside the N T time window.…”
Section: Erp Analysismentioning
confidence: 99%
“…The basal ganglia (151) and pulvinar (152) have also been associated with implicit learning, predictive processing, and distractor filtering (153). Lastly, effects of distractor learning may be expressed in priority maps in frontal and parietal cortex (16,154), as also suggested by studies in non-human primates (120)(121)(122). Plastic changes in priority maps of space in fronto-parietal cortex can account for the fact that attentional priority at a given location is increased or decreased depending on whether that location is associated with a target or a distractor, and observations from behavioral studies that also processing of targets presented at a likely distractor location is impaired (16,65,71), at least when targets and distractors cannot be distinguished at the dimension level (75).…”
Section: Discussionmentioning
confidence: 69%
“…While typically responses in these areas increase as a function of saliency (123,124), as the animals learn to ignore salient distractors, evoked responses to those distractors become smaller than responses elicited by non-salient distractors. In a study by Cosman and colleagues (120), the suppressed FEF response, which was observed once the learned to-be-ignored distractor no longer incurred a behavioral cost, was furthermore followed by a scalp-recorded Pd-like component, suggesting that the frontal eye fields play an important role in implementing inhibition. In combination with previous work showing that V4 responses initially do not differentiate between targets and distractors (125), these findings support the notion that distractor inhibition can be instantiated after distractor learning, once the to-be-suppressed stimulus is physically presented and bottom-up information can be integrated with top-down influences.…”
Section: Post-distractor Inhibition: Pre-attentive and Reactive Inhibmentioning
confidence: 96%
See 1 more Smart Citation